Genetic differentiation between red deer from different sample sites on the Tianshan Mountains (Cervus elaphus), China. (28th November 2014) - Zhou, Can-Lin; Turdy, Risalat; Halik, Mahmut
Abstract: About 273 individuals were identified from 471 fecal samples from six different red deer populations in China. The genetic structure showed that the red deer from the western and eastern Tianshan Mountains was different. A total number of 12 haplotypes were defined by 97 variable sites by the control region (CR), and 10 haplotypes were defined by 34 variable sites by cytochrome b . There was no haplotype sharing between red deer populations from western and eastern Tianshan Mountains by the CR and the cytochrome b . The red deer populations from west were clade with wapiti from North American and red deer from Siberia, while red deer populations from east were clade with red deer from Crimea in Pleistocene rather than west at present. The result of NETWORK also showed that red deer populations from western and eastern Tianshan Mountains were different. The haplotype and the Fst value between western and eastern Tianshan red deer were significantly different. The AMOVA analysis showed that 97.34% and 1.14% of the total genetic variability were found within populations and among populations within groups, respectively, by microsatellite. AMOVA for mitochondria showed that most of the variance was explained among-group. The Fst, pairwise distance, and phylogenetic relationship result showed that red deer between western and eastern Tianshan were more different than some of the red deer from North-Asia, South-Asia, East-Asia, and wapiti. All data from this study do support that the genetic characteristics of red deer between western and eastern Tianshan Mountains by microsatellite, control region, and cytochrome b were different.